Prevalence of hyperglycemia on admission and its effect on short-term cardiovascular outcomes of non-ST elevation myocardial infarction: A retrospective study from a tertiary care center in South India - Amit Mandal; Ramya Iyyadurai; K Fibi Ninan; Karthik Gunasekaran (Archives of Medicine and Health Sciences, 2023)
Background and Aim: Hyperglycemia has a significant negative impact on the morbidity and mortality of patients presenting with acute myocardial infarction. This retrospective study was conducted to determine the short-term clinical outcomes (inhospital mortality, cardiogenic shock, acute heart failure, stroke, fatal arrhythmia, and length of stay) of patients with non-ST-elevation myocardial infarction (NSTEMI) patients and to compare the outcomes in NSTEMI patients with and without hyperglycemia on admission. We also wanted to identify the clinical profile and assess the mortality rates in patients with NSTEMI. Materials and Methods: This retrospective study was conducted over 7 years (April 1, 2014–July 31, 2021). The data were extracted from the inpatient medical records and it was analyzed. All adult patients requiring admission in a single medical unit with a diagnosis of NSTEMI were included in the study. Descriptive statistics were obtained for all variables and entered in MS Excel and analyzed with SPSS (SPSS for Windows, version 16.0, Chicago, IL, USA) in the study, and appropriate statistical tests like P value were employed to ascertain the significance. Factors that were significant in univariate analysis were tested by multivariate regression analysis to identify those that independently predicted poor outcomes. Results: Our study cohort consisted of 260 patients, 144 (55.4%) patients had hyperglycemia on admission (admission blood sugar >200 mg/dl), and 116 (44.6%) had normoglycemia. In our cohort, 166 (63.8%) were male. The most common comorbidity was diabetes mellitus 195 (75%) and 134 (68.7%) diabetic patients had hyperglycemia at presentation. The most common clinical outcome was acute heart failure in 225 (86.5%), followed by cardiogenic shock in 110 (42.3%) patients. Fifteen (5.8%) patients had acute cerebrovascular accident during the hospital stay and 39 (15%) had developed fatal arrhythmias. The mean ± standard deviation duration of hospital stay was of 7.09 ± 5.396 days. The mortality in this cohort was 67 (25.8%). The presence of hyperglycemia on admission was not found to have an effect on mortality (odds ratio [OR]: 0.61, 95% confidence interval [CI]: 0.34–1.10, P = 0.102); however, the presence of hyperglycemia on admission was an independent predictor of cardiogenic shock (OR: 2.18, 95% CI: 1.069–4.483, P = 0.032), acute heart failure (OR: 3.52, 95% CI: 1.44–8.59, P = 0.006), and acute cerebrovascular accident (OR: 13.76, 95% CI: 1.67–112.0, P = 0.015). Conclusions: The presence of hyperglycemia on admission is an independent predictor of short-term outcomes such as cardiogenic shock, acute heart failure, and acute cerebrovascular accident; however, it does not have an effect on inhospital mortality. NSTEMI is associated with significant mortality.